Lack of detection of host associated differences in Newcastle disease viruses of genotype VIId isolated from chickens and geese - Wang Yuyang; Duan Zhiqiang; Hu Shunlin; Kai Yan; Wang Xiaobo; Song Qingqing; Zhong Lei; Sun Qing; Wang Xiaoquan; Wu Yantao; Liu Xiufan (Virology Journal, 2012)
Abstract Background The goose is usually considered to be resistant even to strains of Newcastle disease virus (NDV) that are markedly virulent for chickens. However, ND outbreaks have been frequently reported in goose flocks in China since the late 1990s with the concurrent emergence of genotype VIId NDV in chickens. Although the NDVs isolated from both chickens and geese in the past 15 years have been predominantly VIId viruses, published data comparing goose- and chicken-originated ND viruses are scarce and controversial. Results In this paper, we compared genotype VIId NDVs originated from geese and chickens genetically and pathologically. Ten entire genomic sequences and 329 complete coding sequences of individual genes from genotype VIId NDVs of both goose- and chicken-origin were analyzed. We then randomly selected two goose-originated and two chicken-originated VIId NDVs and compared their pathobiology in both geese and chickens in vivo and in vitro with genotype IV virus Herts/33 as a reference. The results showed that all the VIId NDVs either from geese or from chickens shared high sequence homology and characteristic amino acid substitutions and clustered together in phylogenetic trees. In addition, geese and chickens infected by goose or chicken VIId viruses manifested very similar pathological features distinct from those of birds infected with Herts/33. Conclusions There is no genetic or phenotypic difference between genotype VIId NDVs originated from geese and chickens. Therefore, no species-preference exists for either goose or chicken viruses and more attention should be paid to the trans-species transmission of VIId NDVs between geese and chickens for the control and eradication of ND.